La riforma dell'amministrazione e il sistema universitario tra semplificazione e trasparenza - Orfeo, Maria (Proceedings e report, 2012)
In the reform process that has characterised public administrations for years, simplification and transparency represent two innovative and important aspects for the organisational model of universities. A complex issue that involves multiple profiles and urges a deep reflection on still open questions of significant depth. In their interventions the speakers explore different aspects on the matter, highlighting the reasons for continuing towards an overall change of the administration aimed at making its action more efficient, rapid and economical.